Update to the study protocol, including statistical analysis plan, for the multicentre, randomised controlled OuTSMART trial: a combined screening/treatment programme to prevent premature failure of renal transplants due to chronic rejection in patients with HLA antibodies - Dominic Stringer; Leanne M. Gardner; Janet L. Peacock; Irene Rebollo-Mesa; Rachel Hilton; Olivia Shaw; Richard Baker; Brendan Clark; Raj C. Thuraisingham; Matthew Buckland; Michael Picton; Judith Worthington; et al. (Trials, 2019)
Abstract Background Chronic rejection is the single biggest cause of premature kidney graft failure. HLA antibodies (Ab) are an established prognostic biomarker for premature graft failure so there is a need to test whether treatment decisions based on the presence of the biomarker can alter prognosis. The Optimised TacrolimuS and MMF for HLA Antibodies after Renal Transplantation (OuTSMART) trial combines two elements. Firstly, testing whether a routine screening programme for HLA Ab in all kidney transplant recipients is useful by comparing blinding versus unblinding of HLA Ab status. Secondly, for those found to be HLA Ab+, testing whether the introduction of a standard optimisation treatment protocol can reduce graft failure rates. Methods OuTSMART is a prospective, open-labelled, randomised biomarker-based strategy (hybrid) trial, with two arms stratified by biomarker (HLA Ab) status. The primary outcome was amended from graft failure rates at 3 years to time to graft failure to increase power and require fewer participants to be recruited. Length of follow-up subsequently is variable, with all participants followed up for at least 43 months up to a maximum of 89 months. The primary outcome will be analysed using Cox regression adjusting for stratification factors. Analyses will be according to the intention-to-treat using all participants as randomised. Outcomes will be analysed comparing standard care versus biomarker-led care groups within the HLA Ab+ participants (including those who become HLA Ab+ through re-screening) as well as between HLA-Ab-unblinded and HLA-Ab-blinded groups using all participants. Discussion Changes to the primary outcome permit recruitment of fewer participants to achieve the same statistical power. Pre-stating the statistical analysis plan guards against changes to the analysis methods at the point of analysis that might otherwise introduce bias through knowledge of the data. Any deviations from the analysis plan will be justified in the final report. Trial registration ISRCTN registry, ID: ISRCTN46157828. Registered on 26 March 2013; EudraCT 2012–004308-36. Registered on 10 December 2012.